CUCUMBER BIOFORTIFICATION WITH POTASSIUM - Montoya, S.; Ortega, E.; Navarro, E.; Lorenzo, M.L. (European Scientific Journal, ESJ, 2013)
A few years ago, humans consumed a diet rich in potassium, however, an increased consumption of processed foods and the reduction of the consumption of fruits and vegetables, has meant that potassium intake has been reduced. The aim of this study is to increase potassium content in cucumbers with natural biofortification of the crop, adding an extra amount of potassium sulphate ranging from 0.014 g/l to 4 g/l plus regular fertilization. Fourteen samples were collected at three different times that were analyzed with and without skin. The potassium content was determined by flame photometry. The results show that potassium content has increased over time and the differences initially existing between the cucumbers with and without skin have disappeared.